68‐4: Demonstration of the Novel Ultra‐Slim Flexible Glass as Substrate with Metal Meshed Antenna. Issue 1 (May 2016) - Tseng, Chia-Ying; Chen, Yi-Jiun; Wang, Kai-Jiun; Lin, Jen-Chieh; Garner, Sean; Pollard, Scott; Kuo, Kuan-Ting; Chang, Kao-Der; Lin, Hung-Yi; Wang, Yu-Ming; Lin, Hoang Yan
Abstract : The ultra‐slim flexible glass is demonstrated as the substrate with metal meshed antenna for developing thinner, lighter and fulltransparent smart devices. The linewidth and spacing of the meshed grids are 3 µm and 200–300 µm. The return loss of the mesh antenna has good performance (<10 dB) when operating at 9.5GHz.